The impact of postgraduate training on UK optometrists' clinical decision‐making in glaucoma. (May 2014) - Myint, Joy; Edgar, David F.; Murdoch, Ian E.; Lawrenson, John G.
Abstract Purpose To investigate the impact of a postgraduate training module on optometrists' clinical decision‐making in relation to the diagnosis and management of primary open‐angle glaucoma. Methods A group of United Kingdom community optometrists (n = 53) were assessed immediately before and again 3 months after completing a 3‐day didactic postgraduate university module on the diagnosis and management of glaucoma. A smaller control cohort (n = 20), who did not receive the intervention, was recruited and completed the same assessments on two occasions, separated by approximately 3 months. The assessments comprised: knowledge of five key features of the optic disc in glaucoma, performance on a computer program (Discus) that assessed the ability to differentiate normal from glaucomatous discs and a clinical decision‐making exercise using case‐based scenarios. Results The scores for the knowledge of important disc features for the intervention cohort significantly increased from a median of 2/5 to 5/5 post‐intervention (p < 0.001). For the control cohort, the difference in median scores between the two tests was not significant. Analysing the performance of the intervention cohort using the Discus program showed no significant improvement in ability to diagnose a glaucomatous disc following the intervention [mean area under the receiver operating characteristic curve pre‐intervention = 0.85 (95% CI: 0.76–0.91), post‐intervention = 0.84 (95% CI: 0.76–0.91)]. Similarly, there were no statistically significant differences in mean areas under the receiver operating characteristic curve between tests for the control cohort, although both cohorts compared favourably with a previously published Discus data set from a panel of experts in disc analysis (mean area = 0.87). For the clinical decision‐making exercise the median test score for the intervention cohort was unchanged pre‐ and post‐intervention. Conclusion The results of the present study suggest that a traditional didactic approach, in isolation, is unlikely to be suited to training optometrists to achieve or develop the clinical competencies required for glaucoma detection and management. Consideration should be given to the development of specialist postgraduate training that is more practice‐based, provides opportunities for active learning and includes strategies for feedback and reinforcement.